Emosi Negatif pada Pasien Diabetes Melitus di Puskesmas IV Denpasar Selatan - Ida Ayu Nyoman Putri Bijayanti; Putu Asih Primatanti; Rima Kusuma Ningrum (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Health is a valuable and a highly expected thing by the community during their life. When a person is diagnosed with a disease, it could drive the feeling of anxiety, stress or depression. Diabetes mellitus is a disease with a fairly high prevalence in Indonesia. This study examined the negative emotions suffered by diabetic patients in Puskesmas IV Denpasar Selatan. The subjects were 100 number of the diabetic patients who had fulfilled the criteria. This is a descriptive study with a cross sectional design. The data processed using the Statistical Package for the Social Science (SPSS) with univariate analysis which presented in the table of frequency distribution. The research instrument used the Depression Anxiety Stress Scale 42 (DASS 42) questionnaires as a negative emotion measurement tool suffered by the diabetic patients. The results showed that all the diabetic patients did not experienced depression (100%). Based on the age, the most severe level of anxiety and stress were at >40 years, with severe-very severe anxiety (7%) and mild-moderate stress (27%). Based on the gender, the anxiety and stress were mostly found in the male diabetic patients, with experienced mild-moderate anxiety (25.8%), severe-very severe anxiety (7.6%) and experienced mild-moderate stress (30.3%).